(3fRgI GdebdJjf aj SjQI GdOhdJjf(B:(3GdYdGFjg hGdLdGdjI heGcGf ef GdhbGFY GdJGJGQjIs - (3YHO GdQMef Hf ESeGYjd Hf EHQGgje Hf YKeGf GdTGaYjs ((3CMeO Hf MSf s)
(3ChdgG (B:s
(3GdMeO ddg Ydi LejY GdfYe s
(3BNQgG (B:s
(3hdGjRGd jQO EdjfG ef CNHGQg eYge hLejY ef jhGabg ef edhc GdeSdejf s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdJGQjNs